Practical use of insulin degludec/insulin aspart in a multinational setting: beyond the guidelines. Issue 11 (12th August 2020) - Mehta, Roopa; Chen, Roger; Hirose, Takahisa; John, Mathew; Kok, Adri; Lehmann, Roger; Unnikrishnan, Ambika Gopalakrishnan; Yavuz, Dilek Gogas; Fulcher, Gregory
Abstract: Insulin degludec/insulin aspart (IDegAsp) is a fixed‐ratio co‐formulation of insulin degludec, which provides long‐lasting basal insulin coverage, and insulin aspart, which targets postprandial glycaemia. This review provides expert opinion on the practical clinical use of IDegAsp, including: dose timings relative to meals, when and how to intensify treatment from once‐daily (OD) to twice‐daily (BID) dose adjustments, and use in special populations (including hospitalized patients). IDegAsp could be considered as one among the choices for initiating insulin treatment, preferential to starting on basal insulin alone, particularly for people with severe hyperglycaemia and/or when postprandial hyperglycaemia is a major concern. The recommended starting dose of IDegAsp is 10 units with the most carbohydrate‐rich meal(s), followed by individualized dose adjustments. Insulin doses should be titrated once weekly in two‐unit steps, guided by individualized fasting plasma glucose targets and based on patient goals, preferences and hypoglycaemia risk. Options for intensification from IDegAsp OD are discussed, which should be guided by HbA1c, prandial glucose levels, meal patterns and patient preferences. Recommendations for switching to IDegAsp from basal insulin, premixed insulins OD/BID, and basal‐plus/basal–bolus regimens are discussed. IDegAsp can be co‐administered with other antihyperglycaemic drugs; however, sulphonylureas frequently need to be discontinued or the dose reduced, and the IDegAsp dose may need to be decreased when sodium‐glucose co‐transporter‐2 inhibitors or glucagon‐like peptide‐1 receptor agonists are added. Considerations around the initiation or continuation of IDegAsp in hospitalized individuals are discussed, as well as in those undergoing medical procedures.